Current trends and future directions in koala chlamydial disease research. (November 2017) - Grogan, Laura F.; Ellis, William; Jones, Darryl; Hero, Jean-Marc; Kerlin, Douglas H.; McCallum, Hamish
Abstract: Infectious diseases can be key threatening processes for biodiversity conservation. However, establishing the relative importance of disease (among other threatening processes) as a driver of species declines can be challenging. Bias in the directions that a research field may take as it develops – due to factors such as conservation policy, funding, public perception, and available expertise and technology – may exacerbate this difficulty. Chlamydiosis (infection with bacteria in Family Chlamydiaceae ) is an example of an infectious disease with a poorly understood role in koala ( Phascolarctos cinereus ) population dynamics. The arboreal folivorous koala is an internationally recognized iconic species of high conservation, sociocultural and economic value. To date, no studies have quantitatively examined the breadth and scope of research related to koala chlamydiosis, nor systematically identified the current research gaps. We systematically and quantitatively reviewed a comprehensive database of literature related to koala chlamydiosis, classified and examined the main foci of the research, and evaluated research gaps with the goal of assisting policy planning for funding further koala chlamydiosis research. We examined published literature with regard to journal category, authorship, funding, spatiotemporal scope, study foci and type, chlamydial species examined, methodological design and overall findings. Among the 117 peer-reviewed papers published between 1970 and 2016 that fit our criteria, the most striking finding was the relative lack of population-level disease studies within the last two decades to examine mechanisms of chlamydial infection dynamics. This research gap is of particular concern given the potential role of Chlamydia in koala population declines, and the recent dramatic changes in our understanding of pathogen phylogeny and improved diagnostic approaches. Our results demonstrate a pressing need for future in situ comprehensive longitudinal population-level studies from diverse geographic regions. These studies must utilize up-to-date diagnostic methods capable of distinguishing chlamydial species and strains to elucidate the role of chlamydial infection in koala population declines and the underlying mechanisms involved. They should also employ rigorous epidemiological methodologies and evaluate co-infection, habitat, climatic and demographic data. Our findings suggest some key research gaps concerning koala chlamydiosis, and are hence important for guiding future research into koala chlamydiosis and conservation. Highlights: Population-level studies of chlamydial infection dynamics are comparatively lacking. Hypothesis-testing manipulative experiments were also poorly represented. Future longitudinal studies should focus on robust representative sampling/analysis.